2019
DOI: 10.1371/journal.pone.0224366
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal seed dispersal by dung beetles reduced seed and seedling clumping, but did not increase short-term seedling establishment

Abstract: Dung beetles are secondary seed dispersers, incidentally moving many of the seeds defecated by mammals vertically (seed burial) and/or horizontally as they process and relocate dung. Although several studies have quantified this ecological function of dung beetles, very few have followed seed fate until seedling establishment, and most of these have focused on the effects of seed burial. We know very little about the effects of horizontal seed movement by dung beetles, though it is generally assumed that it wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
0
13
0
1
Order By: Relevance
“…Endozoochory by howler monkeys is largely recognized to result in a higher abundance and richness of seeds in the soil seed bank, and may influence spatial dynamics (Feer et al, 2013;Juliot,;Pouvelle 2009;Santos-Heredia & Andresen, 2014; Urrea-Galeano, Andresen, Coates, Mora-Ardila, & Ibarra-Manríquez, 2019; Urrea-Galeano, Andresen, Coates, Mora-Ardila, Rojas, et al, 2019), and also the higher abundance of seedlings and saplings recruiting under defecation areas compared with control sites (Bravo & Cueto, 2020;Juliot,). It is important to consider, however, that recruits in latrines are likely to be influenced by positive and negative effects: at the same time that latrines represent areas with high income of nutrients (Feeley, 2005;Santos Neves et al, 2010), the higher density of saplings may reduce chances to survive due to negative density-dependent processes (Russo, 2005;Russo and Augspurger, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endozoochory by howler monkeys is largely recognized to result in a higher abundance and richness of seeds in the soil seed bank, and may influence spatial dynamics (Feer et al, 2013;Juliot,;Pouvelle 2009;Santos-Heredia & Andresen, 2014; Urrea-Galeano, Andresen, Coates, Mora-Ardila, & Ibarra-Manríquez, 2019; Urrea-Galeano, Andresen, Coates, Mora-Ardila, Rojas, et al, 2019), and also the higher abundance of seedlings and saplings recruiting under defecation areas compared with control sites (Bravo & Cueto, 2020;Juliot,). It is important to consider, however, that recruits in latrines are likely to be influenced by positive and negative effects: at the same time that latrines represent areas with high income of nutrients (Feeley, 2005;Santos Neves et al, 2010), the higher density of saplings may reduce chances to survive due to negative density-dependent processes (Russo, 2005;Russo and Augspurger, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Both horizontal and vertical distances were dependent on bead size, with the large seed mimics reaching shorter horizontal distances and buried shallower. Previous beetle-mediated seed dispersal studies in tropical forests have demonstrated that the influence of burial depth on the chances of seed germination and establishment are both species and trait-specific (Culot et al, 2011;Griffiths et al, 2016;Leishman et al, 2000;Shepherd & Chapman, 1998;Urrea-Galeano, Andresen, Coates, Mora-Ardila, Rojas, et al, 2019). Yet, burial between 1 and 4 cm, where most of the seed mimics in both latrines and fruit-feeding trees were deposited, are recognized to result in increased germination success and survival when compared with seeds on the soil surface or buried deeper (e.g., Cavalcante, 1991;Shepherd & Chapman, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3.6.1; R Core Team, 2019) using packages 'lme4' (Bates et al, 2015), 'stats' (R Core Team, 2019), 'coxme' (Therneau, 2019), 'car' (J. Fox & Weisberg, 2011), and 'emmeans' (Lenth, 2019).…”
Section: Data Analysesmentioning
confidence: 99%
“…There is evidence that seedling survival is higher when both mammals and dung beetles act together as primary and secondary dispersers, respectively (Culot et al, 2018). Understanding secondary dispersal by dung beetles could be critical to our understanding of forest dynamics and seedling establishment because dung beetles reduce seed clumping (Lawson et al, 2012;Urrea-Galeano et al, 2019), which should decrease density-dependent seed mortality (e.g., pathogen and seed predation) (Andresen & Levey, 2004;Beaune et al, 2012;Bell et al, 2006;Vulinec, 2002). When dung beetles bury seeds, they drastically reduce seed discovery by seed predators.…”
Section: Introductionmentioning
confidence: 99%